2021
DOI: 10.3389/fsurg.2021.597416
|View full text |Cite
|
Sign up to set email alerts
|

Extended Robotic Pulmonary Resections

Abstract: While lung cancer remains the most common cause of cancer-related mortality in the United States, surgery for curative intent continues to be a mainstay of therapy. The robotic platform for pulmonary resection for non-small cell lung cancer (NSCLC) has been utilized for more than a decade now. With respect to more localized resections, such as wedge resection or lobectomy, considerable data exist demonstrating shorter length of stay, decreased postoperative pain, improved lymph node dissection, and overall low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Robotic PN has been gradually developed in recent years. The robotic approach offers many technical advantages, such as accurate identification of tissue planes, better optics, natural movement of the operator's hand is used to control the instrument for safe dissection and more ergonomic ( 37 ). May be better in long-term overall survival of PN.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic PN has been gradually developed in recent years. The robotic approach offers many technical advantages, such as accurate identification of tissue planes, better optics, natural movement of the operator's hand is used to control the instrument for safe dissection and more ergonomic ( 37 ). May be better in long-term overall survival of PN.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the encouraging results obtained by using the robotic-assisted approach in thoracic surgery, it has been possible to extend the indications for this approach also to more challenging procedures [ 19 ]. Meanwhile, the trend of increasing life expectancy makes it necessary to offer the safest surgical approach possible, preferably in association with minimum traumatism, to patients considered frailer, being featured with high perioperative risk.…”
Section: Discussionmentioning
confidence: 99%
“…Scheinerman et al 5 reported another series of 23 patients receiving sleeve lobectomy using RAS with minimal morbidity and without short-term mortality. They designed and used four robotic ports and one assistant port.…”
Section: Discussionmentioning
confidence: 99%
“… 32 (2) In a cohort of 23 cases, there was one case of pneumonia and one of transfusion, but no anastomotic complications. 5 (3) In a cohort of 21 cases, there were two cases of pneumonia, two cases of pyothorax, and only one of anastomotic leak. 33 All of the studies with small sample sizes demonstrated that the incidence of anastomotic complications when using RAS was promisingly low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation